Determination of total phenol, condensed tannin and flavonoid contents and antioxidant activity of Uncaria gambirextracts - M. Jain Kassim; M. Hazwan Hussin; A. Achmad; N. Hazwani Dahon; T. Kim Suan; H. Safley Hamdan (Indonesian Journal of Pharmacy, 2011)
Uncaria  gambir,  a  well  known  Southeast  Asia  plant  have  been  previously used as an alternative medicine for treatment such as diarrheal, sore throat and spongy  gums.  Due  to  its  useful  properties,  in  this  study  we  have  analysed  the total  phenol,  condensed  tannin,  flavonoid  content  and  antioxidant  activity  of Uncaria  gambir in  three  different  solvent  extracts.  Characterization  and quantification analysis using Fourier Transform Infrared (FTIR) spectroscopy and reverse  phase-high  performance  liquid  chromatography  (RP-HPLC)  has confirmed  that  the  major  chemical  constituents  of  Uncaria  gambir are  mainly catechins.  It  was  revealed  that  the  ethyl  acetate  gambir  extract  gives  the highest  catechin  content  and  antioxidant  activity  compared  with  other  solvent extracts.Key words: Uncaria gambir, antioxidant activity, condensed tannin, flavonoid